2020
DOI: 10.4236/ajps.2020.115054
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Indigenous Pesticidal Plants in the Control of Field and Post-Harvest Arthropod Pests in Bambara Groundnuts (<i>Vigna subterranea</i> (L.) Verdc.) in Africa: A Review

Abstract: Bambara groundnuts (Vigna subterranea (L.) Verdc.) is an important leguminous crop native in Africa and is mainly cultivated for its highly nutritious grains. However, bambara groundnuts production is constrained by many insect pests including aphids (Aphids sp.), leaf hopers (Hilda patruelis), foliage beetles (Ootheca mutabilis), pod sucking bugs (Clavigralla tomentosicollis), red spider mites (Tetrunychus sp.), groundnut jassids in the field and bruchids (Callosobruchus maculatus, and Callosobruchus subinnot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…Studies have revealed that important pharmacological properties such as antiproliferative [ 17 ], anti-inflammatory [ 33 ], and insecticidal [ 13 ] activities which were present in C. dichogamus could be attributed to the high concentration of terpenoids [ 34 ] whose presence was also confirmed in the current study. Another study [ 32 ] also indicated that approximately 25 terpenoids were isolated from the root extracts of C. dichogamus .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Studies have revealed that important pharmacological properties such as antiproliferative [ 17 ], anti-inflammatory [ 33 ], and insecticidal [ 13 ] activities which were present in C. dichogamus could be attributed to the high concentration of terpenoids [ 34 ] whose presence was also confirmed in the current study. Another study [ 32 ] also indicated that approximately 25 terpenoids were isolated from the root extracts of C. dichogamus .…”
Section: Discussionsupporting
confidence: 78%
“…It is used in Somalia to treat gonorrhea [ 12 ], arthritis [ 5 ], stomach, and back pains [ 11 , 12 ]. The Mbeere and Afan Oromo communities in Tanzania use dried leaves, roots, and stem barks of C. dichogamus as an antimalarial, antipyretic [ 5 ], and as a pesticide [ 13 ]. In Kitui County, the Kamba community prepares an infusion of the stem bark and leaves of C. dichogamus, locally known as “Mwalula,” for drinking to alleviate back pains, malaria, stomachache, chest problems, fever, oedema, and cough [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Obembe and Kayode observed the insecticidal activity of aqueous extracts from four underutilized tropical plants to protect cowpea seeds from C. maculatus infestation, finding them to be effective and possibly serve as an alternative to synthetic insecticides for the protection of cowpea seeds against bruchids. Based on these findings, it is important to search for bioinsecticides that are effective against some pests, including C. maculatus , to identify extracts and compounds that can be used in integrated management programs, since they are inexpensive and easy to apply and do not cause negative environmental impacts in terms of the risk of toxic residues on seeds . Future studies will be carried out in order to verify the germination effect of the treated and untreated cowpea seeds, as well as to develop an evaluation of the nutritional properties and the effects of the application of the hydroalcoholic fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it is important to search for bioinsecticides that are effective against some pests, including C. maculatus, to identify extracts and compounds that can be used in integrated management programs, since they are inexpensive and easy to apply and do not cause negative environmental impacts in terms of the risk of toxic residues on seeds. 38 Future studies will be carried out in order to verify the germination effect of the treated and untreated cowpea seeds, as well as to develop an evaluation of the nutritional properties and the effects of the application of the hydroalcoholic fraction.…”
Section: ■ Discussionmentioning
confidence: 99%